Safety of Reconstructive Microsurgery in the Elderly Population: a Multicentric Prospective Study. Issue 12 (December 2021) - Cordova, Adriana; Toia, Francesca; Salgarello, Marzia; Pinto, Valentina; Lucattelli, Elena; Sgarzani, Rossella; Figus, Andrea; Cherubino, Mario; Bassetto, Franco; Santanelli di Pompeo, Fabio; Bonfirraro, Pier Paolo; Maruccia, Michele; et al.
Summary: Background: Safety of reconstructive microsurgery in elderly patients is still a topic of debate, because no conclusive evidence exists that provides indications and risk evaluation in elderly patients. The purpose of this study, which the Italian Society for Plastic, Reconstructive, and Aesthetic Surgery (SICPRE) has promoted, is to evaluate the safety and the complication risk of elective reconstructive microsurgery in elderly patients as well as to identify patient- or procedure-related risk factors. The secondary aim is to evaluate the predictive role for complications of the Geriatric 8 score (G8). Methods: A total of 194 consecutive patients from 18 centers, aged 65 or older, who received an elective microsurgical flap between April 2018 and April 2019 were prospectively evaluated. Patient-related, treatment-related, and outcomes data were recorded and statistically analyzed through multiple-adjusted logistic regression models. Results: Our study showed an increased risk of complications and a longer hospitalization in patients aged ≥75 years with the American Society of Anesthesiologists (ASA) score ≥3 (or G8 score ≤11) as compared to patients >65 years of age and <75 years of age who undergo reconstruction with a microsurgical flap. Instead, flap survival did not significantly vary with age, but was associated only with ASA score ≥3 (or G8 score ≤11) and surgeries that last longer than 480 min; however, flap survival (92.3%) was slightly lower than that commonly reported for in the general population. Conclusions: Reconstructive microsurgery in the elderly is generally safe. The ASA score is easier and quicker than the G8 score and equally useful for risk stratification.